MARRIAGE CONTRACTS IN CIVIL LAW: LEGAL SAFEGUARDS FOR CHILDREN’S EDUCATION COSTS IN THE ERA OF EDUCATIONAL AUTONOMY - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2026)
This article analyses marriage contracts under Indonesian civil law as a strategic legal instrument for securing the costs of children’s education in the era of educational autonomy through the Merdeka Curriculum, with two main focuses: (1) the status of marriage contracts under Articles 139–185 of the Civil Code, Article 29 of the Marriage Law, and Constitutional Court Decision No. 69/PUU-XIII/2015, which permits postnuptial agreements; and (2) the potential of specific clauses, such as escrow funds and proportional contributions, to protect children’s rights in accordance with Article 41 of the Marriage Law and Article 9 of the Child Protection Law, in the face of the challenge of variable costs resulting from personalised education. This normative legal research utilises a literature review of legislation, court rulings, and legal literature to conclude that marriage agreements can reduce post-divorce disputes and ensure the continuity of children’s education, in line with Article 31 of the 1945 Constitution and Nadiem Makarim’s ‘Merdeka Belajar’ vision.